Analisi contrastiva delle costruzioni infinitive introdotte da un determinante in italiano e in spagnolo - Szilágyi, Imre (Verbum – Analecta Neolatina, 2009)
The present study aims at drawing a comparison between the 'article + infinitive' constructions in Italian and Spanish. The comparative analysis will tackle both structural questions and the use of these constructions in the two languages. It will be argued that in spite of the extensive similarity of the infinitive preceded by an article (or any other determiner) in Italian and Spanish there are some important divergences that should be noted, too: Italian displays three, Spanish only two subtypes of the basic pattern. Our contrastive analysis allows us to make some more general observations concerning the syntax of Italian and Spanish, in particular with regards to the expression of the subject.